The broken gun - L'Amour, Louis, 1908-1988 (Louis L'Amour hardcover collection, 1985)
Novelist Dan Sheridan takes to the Old West to visit what is believed to be a ranch once owned by the famed Toomey brothers. However, he soon comes face-to-face with a duo of salty murderers.